Proceedings of the Proceedings of the 1st Conference of Visual Art, Design, and Social Humanities by Faculty of Art and Design, 2020
DOI: 10.4108/eai.2-11-2019.2294862
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Environmental Issues in Electronic Module of Social Studies Learning in Junior High School

Abstract: Education related to environmental issues must be integrated into interactive learning media. One of them is on the electronic module. This challenge is in line with developments in the 21st century, which are interdependent between the environment, economy and technology. This should be a concern for all parties, especially the facts at school that show that social studies learning is not in accordance with the intended learning objectives of the social studies itself. This research is descriptive research. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, interactive e-modules can be used in both online and offline classrooms (Adawiyah, R., and Susilawati, L. A. 2020;Danirmala, 2020;Dankbaar, 2017;Erna, M., and Anwar, L. 2021;Fadieny, N., and Fauzi, A, 2021;Hendriyani, Y., Ambiyar, S., and Effend A number of studies, such as Cloonan et al, (2020), back up this claim, showing that students, both experienced and new to the subject, gain knowledge and confidence as a result. McNamara et al (2020) conducted research that found that online interactive e-modules played an important role in improving students' critical thinking skills and providing them with greater independence in the process of skill improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, interactive e-modules can be used in both online and offline classrooms (Adawiyah, R., and Susilawati, L. A. 2020;Danirmala, 2020;Dankbaar, 2017;Erna, M., and Anwar, L. 2021;Fadieny, N., and Fauzi, A, 2021;Hendriyani, Y., Ambiyar, S., and Effend A number of studies, such as Cloonan et al, (2020), back up this claim, showing that students, both experienced and new to the subject, gain knowledge and confidence as a result. McNamara et al (2020) conducted research that found that online interactive e-modules played an important role in improving students' critical thinking skills and providing them with greater independence in the process of skill improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Then the social environment is a sociological examination, which means a highlight based on relationships between people, Yuliani, 2018) relations between groups, and relationships between people and groups in the process of social life (Danirmala et al, 2020a)". The statement above is consistent with the view (Yumaroh, 2024) that "social environment involves conditions, conditions, and interactions between humans one with another.…”
Section: Introductionmentioning
confidence: 99%